Exploiting multiferroicity of TbFeO3 nanoparticles for hydrogen generation through photo/electro/photoelectro-catalytic water splitting. (15th February 2023) - Khan, Huma; Lone, Irfan Hussain; Lofland, Samuel Edward; Ramanujachary, Kandalam Venkata; Ahmad, Tokeer
Abstract: Hydrogen is a potential future energy source that could replace conventional fuel and provide the necessary energy. Multiferroic materials are the most likely choices for water splitting due to their ferroelectric characteristics and ability to function as magnetically recoverable catalysts. Multiferroic terbium orthoferrite nanoparticles were synthesized at low temperature by the polymeric citrate precursor route to study the photocatalytic, electrocatalytic and photoelectrochemical activity towards hydrogen production. Powder X-ray diffraction revealed successful formation of orthorhombic TbFeO3 nanoparticles. A larger aspect ratio of 3.9 and a bandgap of 2.13 eV were seen in the elongated TbFeO3 nanoparticles, which contributes to the photo/electro-catalytic activity. Magnetic and ferroelectric studies revealed weak ferromagnetism and ferroelectric polarization of 0.037 μC cm −2 in TbFeO3 nanoparticles, confirming multiferroicity. Visibly active and multiferroic TbFeO3 nanoparticles showed notable hydrogen evolution of 1.44 mmol h −1  g −1 . In electrocatalytic and photoelectrochemical water splitting investigations, TbFeO3 nanoparticles demonstrated current densities of 30 and 60 mA cm −2, respectively. EIS, TRPL, transient photocurrent and Mott-schottky measurements were used to examine charge transfer kinetics. The high H2 evolution and good OER/HER tests were attributed to increased charger separation efficiency due to ferroelectricity induced band bending. Graphical abstract: Image 1 Highlights: Multiferroic orthorhombic TbFeO3 NPs stabilized by low temperature precursor route. Morphological studies show elongated nanoparticles with aspect ratio of 3.9. Significant photocatalytic H2 evolution rate of 1.44 mmol h −1  g −1 . High OER/HER/photocurrent density in TbFeO3 NPs is reported.